A novel in situ gas stripping‐pervaporation process integrated with acetone‐butanol‐ethanol fermentation for hyper n‐butanol production. Issue 1 (14th July 2015) - Xue, Chuang; Liu, Fangfang; Xu, Mengmeng; Zhao, Jingbo; Chen, Lijie; Ren, Jiangang; Bai, Fengwu; Yang, Shang‐Tian
ABSTRACT: Butanol is considered as an advanced biofuel, the development of which is restricted by the intensive energy consumption of product recovery. A novel two‐stage gas stripping‐pervaporation process integrated with acetone‐butanol‐ethanol (ABE) fermentation was developed for butanol recovery, with gas stripping as the first‐stage and pervaporation as the second‐stage using the carbon nanotubes (CNTs) filled polydimethylsiloxane (PDMS) mixed matrix membrane (MMM). Compared to batch fermentation without butanol recovery, more ABE (27.5 g/L acetone, 75.5 g/L butanol, 7.0 g/L ethanol vs. 7.9 g/L acetone, 16.2 g/L butanol, 1.4 g/L ethanol) were produced in the fed‐batch fermentation, with a higher butanol productivity (0.34 g/L · h vs. 0.30 g/L · h) due to reduced butanol inhibition by butanol recovery. The first‐stage gas stripping produced a condensate containing 155.6 g/L butanol (199.9 g/L ABE), which after phase separation formed an organic phase containing 610.8 g/L butanol (656.1 g/L ABE) and an aqueous phase containing 85.6 g/L butanol (129.7 g/L ABE). Fed with the aqueous phase of the condensate from first‐stage gas stripping, the second‐stage pervaporation using the CNTs‐PDMS MMM produced a condensate containing 441.7 g/L butanol (593.2 g/L ABE), which after mixing with the organic phase from gas stripping gave a highly concentrated product containing 521.3 g/L butanol (622.9 g/L ABE). The outstanding performance of CNTs‐PDMS MMM can be attributed to the hydrophobic CNTs giving an alternative route for mass transport through the inner tubes or along the smooth surface of CNTs. This gas stripping‐pervaporation process with less contaminated risk is thus effective in increasing butanol production and reducing energy consumption. Biotechnol. Bioeng. 2016;113: 120–129. © 2015 Wiley Periodicals, Inc. Abstract : An in situ two‐stage gas stripping‐pervaporation process coupled with acetone‐butanol‐ethanol fermentation could produce more than 500 g/L butanol. The process uses gas stripping as the first‐stage and carbon nanotube mixed membrane for the second‐stage pervaporation.